Analysis of Community Learning to Support Tangkas Lake Ecotourism Development, Muaro Jambi Regency - Bambang Hariyadi; Agus Subagyo; Winda Dwi Kartika; Rio Zulkarnain (Quagga: Jurnal Pendidikan dan Biologi, 2023)
Tangkas Lake is a riparian lake, a relatively new tourist destination in Muaro Jambi Regency. The increasing number of tourists visiting this natural destination is expected to cause various problems, especially social problems among fellow citizens. For this reason, it is necessary to have a good understanding of the local community regarding ecotourism. This study aims to analyze the sociocultural characteristics of the local community related to learning that can sustainably support Tangkas Lake ecotourism. The research was conducted with a qualitative approach. Data were collected employing a participatory manner through focused discussions. In addition, data were also collected through in-depth interviews and semi-structured interviews using a questionnaire. In general, the knowledge of local people regarding ecotourism is in a low category. In terms of perceptions and attitudes, the people have good perceptions and attitudes regarding Tangkas Lake tourism activities. Men tend to have a more positive attitude than women. In contrast, women tend to have better perceptions regarding Tangkas Lake tourism. For this reason, efforts to strengthen (increase) public understanding are needed to improve local people's awareness of the importance of educational content in tourism activity. In addition, the community also needs to be facilitated to increase their understanding of ecotourism and seven tourism charming (sapta pesona).